Fraud, exaggerations, and ghost authorship: questioning the reliability of the scholarly record - Bordignon, Frédérique; Cabanac, Guillaume; Labbé, Cyril; Bernisson, Maud (HAL (Le Centre pour la Communication Scientifique Directe), 2023)
National audience